APPROACHES TO THE DEVELOPMENT OF PEDIATRIC PALLIATIVE CARE - Nekhanevych, O. B.; Manin, M. O.; Grishunina, N. Yu. (Rehabilitation and Recreation, 2023)
Considering today’s challenges to medicine and provision of social protection to vulnerable population groups, the issue of developing pediatric palliative care is relevant and crucial. The aim of the study is to analyze the development level of pediatric palliative care in Ukraine and European countries. Material and methods: analysis and generalization of data from scientific-methodological and specific literature, documentary materials, information resources on the Internet, and regulatory and legal frameworks of Ukraine, the Republic of Poland and the Republic of Italy. Research results. The goal of pediatric palliative care is to support the child and their family as soon as a life-threatening disease is diagnosed. Such care is provided throughout the entire trajectory of the child’s disease. Pediatric palliative care is aimed at improving the level of physical, mental, and spiritual well-being of the child and their family within the limits of the diagnosed incurable, often progressive, disease. The solution of multidisciplinary tasks requires the work of an interdisciplinary team in a palliative inpatient department, a mobile crew, and assistance at home. The family-centered model of pediatric palliative care is one of the unique models of supporting the family to adhere to a series of socio-medical interventions and maintenance of intra-family communication, avoid social deprivation of the family, and promote and coordinate the care of a child with an incurable disease. Conclusions. Palliative pediatric care contributes to the improvement of the quality of life of the child and their family. Pediatric palliative care in Ukraine and the world needs solving a range of problems related to financing and specialized education of specialists and parents of the child. The functioning of the inpatient and mobile pediatric palliative care team should be coordinated and continuous. The family-centered model is an effective approach to pediatric palliative care for the child and family.